Pendampingan (Konseling) Pastoral kepada Orang yang Sulit Mengampuni - Sihotang, Eleven (JURNAL DIAKONIA, 2021)
This article offers a model of pastoral counseling assistance for someone who is difficult to forgive and accept dark events. The model proposed in this paper is by building sympathetic relationships, assistance is carried out using the empty chair technicque and religious facilities. The type of research used in this paper is literature or literature study. The findings of this paper show that someone can forgive and accept dark events by imitating Jesus.